2020
DOI: 10.2967/jnumed.120.245084
|View full text |Cite
|
Sign up to set email alerts
|

FAPI-74 PET/CT Using Either18F-AlF or Cold-Kit68Ga Labeling: Biodistribution, Radiation Dosimetry, and Tumor Delineation in Lung Cancer Patients

Abstract: Ga-FAPI-2/4/46 have already been proposed as promising PET-tracers. However, the short half-life of 68 Ga (T1/2 68 min) creates problems with manufacture and delivery. 18 F (T1/2 110 min) labeling would result in a more practical large scale production and a cold-kit formulation would improve the spontaneous availability. The NOTA-chelator ligand FAPI-74 can be labeled with both 18 F-AlF (Aluminum-Fluoride) and 68 Ga. Here we describe the in-vivo evaluation of 18 F-FAPI-74 and a proof-of-mechanism of 68 Ga-FAP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
205
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 194 publications
(229 citation statements)
references
References 38 publications
(38 reference statements)
12
205
0
Order By: Relevance
“…Other publications report the propensity of FAP-specific PET to detect more NSCLC metastases than FDG PET, but patient collectives were too small to analyze whether this translates to more accurate staging. Figure 2) [24]. Applying a 3-fold threshold compared to healthy-appearing normal tissue resulted in volumes equal to those created by CT-based contouring (69.8 mL with FAP-specific PET vs. 67.4 mL with CT).…”
Section: Lungmentioning
confidence: 90%
See 2 more Smart Citations
“…Other publications report the propensity of FAP-specific PET to detect more NSCLC metastases than FDG PET, but patient collectives were too small to analyze whether this translates to more accurate staging. Figure 2) [24]. Applying a 3-fold threshold compared to healthy-appearing normal tissue resulted in volumes equal to those created by CT-based contouring (69.8 mL with FAP-specific PET vs. 67.4 mL with CT).…”
Section: Lungmentioning
confidence: 90%
“…Giesel & Adeberg et al used a newer compound, FAPI-74, for target volume delineation in 10 patients with non-small-cell lung cancer (NSCLC, 8 adenocarcinomas, 2 squamous cell carcinomas, Figure 2) [24]. Applying a 3-fold threshold compared to healthy-appearing normal tissue resulted in volumes equal to those created by CT-based contouring (69.8 mL with FAP-specific PET vs. 67.4 mL with CT).…”
Section: Lungmentioning
confidence: 99%
See 1 more Smart Citation
“…with gallium-68 and fluor-18, resulting in [ 68 Ga]Ga-FAPI-74 and [ 18 F]F-FAPI-74, respectively (Giesel et al 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Toms et al [ 102 ] synthesized an 18 F-labelled FAPI ([ 18 F]FGlc-FAPI) and concluded from a preclinical study it is an interesting candidate for translation to the clinic, taking advantage of the longer half-life and physical imaging properties of 18 F. Giesel et al [ 113 ] describe the NOTA-chelator ligand FAPI-74 that can be labeled with both Al [ 18 F]F and 68 Ga. In ten patients with lung cancer PET-scans were acquired after administration of [ 18 F]F-FAPI-74, with the highest contrast achieved 1 h p.i.…”
Section: Targeting Cafs For Imaging and Therapymentioning
confidence: 99%